2010
DOI: 10.1007/s10549-010-0854-7
|View full text |Cite
|
Sign up to set email alerts
|

COX2 expression in prognosis and in prediction to endocrine therapy in early breast cancer patients

Abstract: In breast cancer, the prognostic impact of COX2 expression varies widely between studies. We examined the prognostic value of COX2 expression in a large cohort of breast cancer patients treated with primary surgery between 1985 and 1994 and explained the variable results of COX2 expression found in the literature. A tissue microarray was constructed of available tumour material, and ER, PgR, HER2, Ki67 and COX2 were examined by immunohistochemistry. Median follow-up was 19 years. Fifty-five percent (n = 369/67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 30 publications
(33 reference statements)
2
50
0
1
Order By: Relevance
“…A total of 33.0% of our sample cohort exhibited COX-2 expression (using the 5% threshold), which is similar to the results of previous studies (24)(25)(26)(27)(28)(29)(31)(32)(33)(34). In congruence with previously published reports, we observed a significant association between COX-2 expression and high tumor grade (26)(27)(28)30,32,33) and also identified a significant association between COX-2 expression and TNBC. The association between TNBC status and high tumor grade (OR=8.89, 95% CI: 3.12-28.55; P<0.001) was in agreement with results of larger studies (12,13,15,16,18,22).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A total of 33.0% of our sample cohort exhibited COX-2 expression (using the 5% threshold), which is similar to the results of previous studies (24)(25)(26)(27)(28)(29)(31)(32)(33)(34). In congruence with previously published reports, we observed a significant association between COX-2 expression and high tumor grade (26)(27)(28)30,32,33) and also identified a significant association between COX-2 expression and TNBC. The association between TNBC status and high tumor grade (OR=8.89, 95% CI: 3.12-28.55; P<0.001) was in agreement with results of larger studies (12,13,15,16,18,22).…”
Section: Discussionsupporting
confidence: 91%
“…Studies using in vitro breast cancer cell lines and in vivo mouse models have demonstrated that COX-2 overexpression plays key roles in tumorigenesis by stimulating epithelial cell proliferation, inhibiting apoptosis, stimulating angiogenesis, increasing multidrug resistance and enhancing cell motility and invasion (15)(16)(17)(18)(19)(20)(21)(22)(23). The evidence supporting the role of COX-2 in breast cancer progression has also been demonstrated in clinical studies; patients with COX-2-expressing primary tumors exhibited shortened disease-free and overall survival (24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Patients with bilateral tumors or a prior history of cancer (other than basal cell carcinoma or cervical carcinoma in situ) were excluded. The following data were known: age, tumor grade, histological type, Tumor-Node-Metastasis stage, local and systemic therapy, locoregional/distant tumor recurrence, secondary tumor, survival, and expression of estrogen receptor (ER), progesterone receptor, and human epidermal growth factor receptor 2 (HER2) (23). All tumors were graded according to current pathological standards by a pathologist (V.T.H.B.M.…”
Section: Patients and Tumorsmentioning
confidence: 99%